Effects of acclimation to long-term shading on photosynthesis in grapevines: roles of non-structural carbohydrates and stomatal conductance - Gallo, Agustina Eugenia; Christophe, Angélique; Poupard, Magali; Boulord, Romain; Rolland, Gaëlle; Prieto, Jorge Alejandro; Simonneau, Thierry; Pallas, Benoît (Wiley, 2024)
Plant acclimation to varying light environments can enhance productivity. However, limited research exists on how plants re-acclimate to sunlight after shading, despite the increasing use of transient crop shading techniques to mitigate climate change impacts. This study focused on grapevine, a species highly responsive to shade, to explore the effects of prolonged shading on photosynthetic re-acclimation of plants upon sun re-exposure. An experiment was conducted using pot-grown plants subjected to different shading durations and then transferred to sunlight conditions. Results varied depending on whether leaves developed under sun or shade and on the duration of shading. Under shade, stomatal conductance decreased by up to 50%, while photosynthesis was reduced by 30–60%, with longer shading periods causing a greater decrease. Upon sun re-exposure of shaded plants, sun-developed leaves gradually reached 100% of the stomatal conductance of sun-control plants, but their photosynthesis remained at 70%. Despite reduced photosynthesis, analyses of non-structural carbohydrate (NSC) contents revealed that carbohydrate pools were maintained in shaded leaves, likely due to reduced carbon demand by plant sinks under shade. The maintenance of NSC limited optimal photosynthetic recovery upon sunlight re-exposure. In contrast, shade-developed leaves did not increase photosynthesis upon transfer to sunlight due to irreversible morphological changes. This study provides new insights into the impact of shade acclimation on biochemical, physiological and morphological processes when plants are subjected to changing light environments.